Geospatial Metadata for Discovery in Scholarly Publishing - Niers, Tom; Nüst, Daniel (Septentrio Conference Series, 2020)
See RECORDING of the presentation (starts at 00:12:00) and a demonstration of the plugin. Many scientific articles are related to specific regions of the Earth. The connection is often implicit, although geospatial metadata has been shown to have positive effects, such as detecting biases in research coverage or enhancing discovery of research. Scholarly communication platforms lack an explicit modelling of geospatial metadata. In this work, we report a novel approach to integrate well-defined geospatial metadata into Open Journal Systems (OJS). Authors create complex geometries to represent the related location(s) or region(s) for their submission and define the relevant time period. They are assisted by an interactive map and a gazetteer to capture high quality coordinates as well as a matching textual description with high usability. The geospatial metadata is published within the article pages using semantic tags, integrated in standardised publication metadata, and shown on maps. Thereby, the geoOJS plugin facilitates indexing by search engines, can improve accessibility, and provides a foundation for more powerful map-based discovery of research articles across journals. See the Extended Abstract PDF for more details.